Effects of Understory or Overstory Removal on the Abundances of Soil Nematode Genera in a Eucalyptus Plantation - Gao, Dandan; Wan, Songze; Fu, Shenglei; Zhao, Jie (Frontiers in Plant Science, 2021)
In south China, eucalyptus plantations typically consist of a single-species overstory (a eucalyptus monoculture) and a dense understory of a dominant fern species. In the current study, we assessed the effects of four treatments [control (CK), understory removal (UR), tree removal (TR), and all-plant removal (PR)] on the abundances of soil nematode genera, which can provide insight into the ecological functions of understory plants and trees. Soil nematodes were sampled six times (once before and five times after treatments were implemented) at 0–5 and 5–10 cm soil depths. The temporal dynamics of nematode genera were analyzed by the principle response curves (PRC) method. At 0–5 cm depth, the abundances of most nematode genera rapidly increased shortly after vegetation removal but then gradually decreased; the effects of UR were stronger than the effects of TR. The results might be explained by the pulsed input of plant debris to soil and its subsequent depletion. At 5–10 cm depth, the nematode communities were relatively unaffected by vegetation removal within the first 162 days, but the abundances of most genera sharply decreased on day 258 and then sharply increased on day 379 (the last sampling time). The results indicated that most nematode genera, even r-selected genera, were sensitive to vegetation removal in the upper soil layer and that understory vegetation can greatly affect soil nematode communities and presumably soil food webs. The nematode genera Prismatolaimus and Diphtherophora may be good indicators of the effects of vegetation removal. The results increase our understanding of the relationships between soil nematode genera and forest plant communities and of how soil biota is affected by forest management practices.